2020
DOI: 10.1155/2020/1072675
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass Loss and Sarcopenia in Ecuadorian Patients

Abstract: Introduction. An intimate relationship between osteoporosis and sarcopenia has been established. At present, there are few epidemiological studies about osteosarcopenia due to the recent use of this term, especially in Latin America. Objective. To study the association between osteoporosis and sarcopenia and determine the prevalence of osteosarcopenia in patients who attended a rheumatology center in Ecuador. Methods. A cross-sectional study was conducted in a population of patients who had a densitometric stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
2
10
0
2
Order By: Relevance
“…Turning to body composition association with T-score, in Swiss study, men with sarcopenia, which was characterized as skeletal muscle mass index lower or equal to 7.26 kg/m 2 , had signi cantly lower femoral neck T-score compared to men, who had higher skeletal muscle mass index [25]. Furthermore, Intriago and colleagues found that in older adults with osteoporosis lean mass, appendicular lean mass and SMMI were lower than in older adults without sarcopenia [26]. However, the majority of participants in that study were women.…”
Section: Discussionmentioning
confidence: 98%
“…Turning to body composition association with T-score, in Swiss study, men with sarcopenia, which was characterized as skeletal muscle mass index lower or equal to 7.26 kg/m 2 , had signi cantly lower femoral neck T-score compared to men, who had higher skeletal muscle mass index [25]. Furthermore, Intriago and colleagues found that in older adults with osteoporosis lean mass, appendicular lean mass and SMMI were lower than in older adults without sarcopenia [26]. However, the majority of participants in that study were women.…”
Section: Discussionmentioning
confidence: 98%
“…Turning to body composition association with T-score, in a Swiss study, men with sarcopenia, which was characterized as skeletal muscle mass index lower or equal to 7.26 kg/m 2 , had significantly lower femoral neck T-scores compared to men who had higher skeletal muscle mass index [ 27 ]. Furthermore, Intriago and colleagues found that in older adults with osteoporosis lean mass, appendicular lean mass and SMMI were lower than in older adults without sarcopenia [ 28 ]. However, the majority of participants in that study were women.…”
Section: Discussionmentioning
confidence: 99%
“…In the Hertfordshire Cohort Study, muscle size and muscle strength were positively associated with bone size and strength [18]. Greater loss of bone mass was noted in CONTACT C. Cooper cc@mrc.nhs.uk NIHR Southampton Biomedical Research Centre, University of Southampton and University Hospitals Southampton NHS Foundation Trust, Tremona Road, Southampton, SO16 6YD, UK osteosarcopenic patients compared to osteoporotic patients in a study conducted in Ecuador dominated by female participants [19]. A positive relationship between muscle and bone mass decline over a year was recognized in older individuals in the SarcoPhAge study [20], whereas an increase in the risk of fracture and a decline in muscle strength were associated with a decrease in spine and hip BMD [20].…”
Section: Coexistence Of Poor Bone and Muscle Measurementsmentioning
confidence: 99%